Akhlak dan Kebahagiaan Hidup Ibnu Miskawaih - Ernita Dewi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
Moral is the first asset to attain happiness of life. By pure moral, one will be motivated to do goodness and give benefit to others. The true happiness is not gauged from property and other material life. But it is internal and spiritual achievement to be grateful for every grace given by Allah. Ibnu Maskawaih argues that one who has noble moral, as it is the first asset to achieve happiness, will reach the true happiness. The reality of human‟s life nowadays, which is corrupted by the crisis and moral degeneration turning people from good to bad and tyranny, can be guided to the goodness by teaching and practicing noble moral from early childhood. All educational subjects have to be directed to create a noble  moral in order people spirits are trained to do goodness and used with noble values